Challenges of Communicating in Intercultural Communities - Wafa Ali Abd Elrazg Mktad (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2025)
This research paper sheds light on important topic which is the insensitivity in intercultural communication; that is to say, a lack of awareness and consideration for cultural differences such as values, norms, nonverbal cues of others. This lack can hinder the success in intercultural communication as a result of biases or stereotypes. By understanding this serious problem and knowing how to handle it effectively by creating atmosphere that allows interlocutors get ’’’ deep understanding" of others’ cultures, beliefs and so on, so we can reduce or finish this obstacle. Data collected by using ordinal scale as a tool of measurement by reporting data in a form of ranking and ordains without confirming the variations’ degrees between them. Type of this research is quantitative as it well known that data collected by ordinal scale is quantitative data. Data collected by using self-assessment questionnaire, which is adapted form. Participants number is 40, as they have chosen based on their experience of living abroad. The result, of data analysis indicated different interpretations that all leads to only one fact which deep understanding of other’ cultural difference is a key factor in communicating successfully." respect, respect, and respect even if they are different "